Ethnobotanical study of medicinal plants used to treat osteoarticular diseases in the Moroccan Rif, Morocco - Noureddine Chaachouay; Ouafae Benkhnigue; Mohamed Fadli; Rachida El Ayadi; Lahcen Zidane (GarVal Editorial Ltda., 2019)
Context: Ethnobotanical studies are one of the important steps in bioprospecting and preserving traditional uses of medicinal plants. Aims: To identify medicinal and aromatic plants used by the local people to treat osteoarticular diseases, together with the associated ethnomedicinal knowledge. Methods: The ethnobotanical survey was conducted in the Moroccan Rif region (North of Morocco) for two periods from 2016 to 2018. In total, 520 local traditional herbalists and users of these plants were interviewed. Information was collected using semi-structured interviews and group discussion, analyzed and compared by quantitative ethnobotanical indices such as family importance value (FIV), relative frequency of citation (RFC), plant part value (PPV), fidelity level (FL) and informant consensus factor (ICF) were used to analyze the obtained data. Results: The analysis of results identified 17 plant species distributed in 10 families with a dominance of the Poaceae (6 species). Concerning the diseases treated, rheumatism diseases have the highest ICF (0.98). The survey revealed that leaves were the most used part of the plants (PPV=0.37) and the majority preparation used was a decoction (40.9%). Conclusions: The results of the present study showed the existence of indigenous ethnomedicinal knowledge of medicinal and aromatic plants in the Moroccan Rif to treat osteoarticular diseases. Further research on phytochemical, pharmacological and other biological activities should be considered to discover new drugs from these documented plants.